Antioxidant activity of crude extracts and essential oils from flower buds and leaves of Cistus creticus and Cistus salviifolius - Sultan T. Abu-Orabi (Arabian Journal of Chemistry, 2020)
Volatile oils from flowers and leaves of C. creticus L. and C. salviifolius L. were extracted by two extraction methods; namely, hydrodistillation and solid-phase micro-extraction (SPME). The chemical composition of essential oils was analyzed by GC and GC–MS. The volatile extracted from leaves and flowers of C. criticus using SPME was dominated by monoterpenes and sesquiterpenes hydrocarbon with α-pinene, camphene and α-cubebene as major components. In hydrodistillation, the oil extracted from leaves was dominated by oxygenated diterpenes and diterpenes hydrocarbon with manoyl oxide and sclarene as major components, whereas, the oil extracted from flowers was dominated by oxygenated diterpenes and diterpenes hydrocarbon with manoyl oxide and abietatriene as major components. The volatile from flowers and leaves of C. salviifolius obtained by SPME were dominated by monoterpenes and sesquiterpenes with δ-3-carene, α-pinene, β-pinene, and E-caryophyllene as major constituents. On the other hand, the oils from flowers and leaves of C. salviifolius obtained by hydrodistillation were dominated by oxygenated diterpenes, diterpenes hydrocarbon and esters with dehydro abietol, abietol, manoyl oxide and methyl octadecenoate as major components. In the leaves, the major components of the oil were manoyl oxide, E-ethyl cinnamate, and Z-ethyl cinnamate. These oils showed weak antioxidant activity when compared to the positive controls α-tocopherol, ascorbic acid, and EDTA, while the crude extracts aq. MeOH, butanol, and water showed good antioxidant activity. Discriminating between the studied plants based on the extraction method was also possible upon applying Principle component analysis (PCA) to the obtained GC–MS data.